Empowering Diabetes Self-Management Through Technology and Nurse Health Coaching. Issue 6 (December 2019) - Miyamoto, Sheridan; Henderson, Stuart; Fazio, Sarina; Saconi, Bruno; Thiede, Elizabeth; Greenwood, Deborah A.; Young, Heather M.
Purpose: This research explores the impact of mobile health (mHealth) technology and nurse health coaching on views of diabetes self-management (DSM) for persons living with diabetes. Methods: Three focus groups (N = 24) were conducted with individuals living with type 2 diabetes who participated in a nurse health coaching and mHealth technology intervention study. Qualitative thematic analysis was used to identify overarching themes in each group. Results: Major themes identified following intervention participation included enhanced perspectives about living with diabetes, increased awareness of how health behaviors influence DSM, improved support, and increased ownership of DSM. Conclusions: The themes identified suggest that the mHealth technology and health coaching intervention together may have had an empowering effect on participants' DSM. These results suggest that providing nurse health coaching with mHealth technology may help individuals ameliorate some of the challenges of living with and managing diabetes.